Mortality and cancer incidence in a cohort of meatworkers. Issue 9 (22nd August 2003) - Fritschi, L; Fenwick, S; Bulsara, M
Abstract : Aims: To determine the risk of all cause mortality, cause specific mortality, and incident cancer in meatworkers. Methods: In a retrospective cohort study, a list of members of a meatworkers union in Australia was matched with the national death and cancer registries. Standardised mortality ratios (SMR) and standardised incidence ratios (SIR) were calculated using Australian population rates. Exposure to animal viruses, animal blood, animal faeces, and plastic pyrolysis products was assigned according to job title. A nested case control analysis examined the risk of mortality and cancer incidence by each exposure. Results: There were approximately 20 000 subjects available for analysis. Male workers had increased risk of mortality from all causes (SMR 116, 95% CI 105 to 128) and from injury (SMR 131, 95% CI 108 to 157). Risk of incident lung cancer in males was non-significantly increased (SIR 164, 95% CI 97 to 259) and males had a raised risk of head and neck cancer (SIR 188, 95% CI 103 to 315). There were no significant associations with specific exposures. Conclusions: Compared to the general Australian population, meatworkers have increased risk of death from all causes, death from injury, and incident lung and head and neck cancer. Analysis by occupational exposures did not disclose any strong evidence of specific occupational risk factors, although this analysis was limited by small numbers of some outcomes and exposure assessment which was based on job titles only.